Role and Mechanisms of Tumor-Associated Macrophages in Hematological Malignancies - Xie, Yutong; Yang, Huan; Yang, Chao; He, Liren; Zhang, Xi; Peng, Li; Zhu, Hongbin; Gao, Lei (Frontiers in Oncology, 2022)
Mounting evidence has revealed that many nontumor cells in the tumor microenvironment, such as fibroblasts, endothelial cells, mesenchymal stem cells, and leukocytes, are strongly involved in tumor progression. In hematological malignancies, tumor-associated macrophages (TAMs) are considered to be an important component that promotes tumor growth and can be polarized into different phenotypes with protumor or antitumor roles. This systematic review emphasizes research related to the role and mechanisms of TAMs in hematological malignancies. TAMs lead to poor prognosis by influencing tumor progression at the molecular level, including nurturing cancer stem cells and laying the foundation for metastasis. Although detailed molecular mechanisms have not been clarified, TAMs may be a new therapeutic target in hematological disease treatment.